การปฏิบัติการพยาบาลขั้นสูงในการดูแลเท้าของผู้สูงอายุโรคเบาหวาน - ศิรินิยมชัย รุ่งศักดิ์ (Nursing Research and Innovation Journal, 2014)
บทคัดย่อ: การเกิดแผลที่เท้าในผู้สูงอายุโรคเบาหวานเป็นภาวะแทรกซ้อนที่มักต้องใช้เวลานานในการรักษาและเสี่ยงต่อความพิการจากการถูกตัดเท้าหรือตัดขา ส่งผลกระทบทั้งทางด้านร่างกาย จิตใจ อารมณ์ สังคม และเศรษฐกิจ บทความนี้มีวัตถุประสงค์เพื่อนำเสนอการจัดการดูแลเท้าผู้สูงอายุโรคเบาหวานและการพัฒนาคุณภาพการดูแลเท้าผู้สูงอายุโรคเบาหวาน โดยประยุกต์บทบาทของปฏิบัติการพยาบาลขั้นสูงที่ครอบคลุมการประเมินปัญหา การจัดการดูแลอย่างต่อเนื่องจากโรงพยาบาลไปถึงบ้านและในชุมชน คำสำคัญ: การปฏิบัติการพยาบาลขั้นสูง การดูแลเท้า ผู้สูงอายุ โรคเบาหวาน Abstract: Foot ulcers are a major complication in older adults with diabetes mellitus. Diabetic foot ulcers usually receive long term treatment and risk for deformity from foot amputation or leg amputation which results in physical, emotional, mental, social,and financial consequences. This article aims to explore the foot care management and the development in quality of foot care for older adults with diabetes mellitus. The advanced practice nurses’ roles were applied, regarding comprehensive health assessment, care management, and continuing care from hospital to community. Keywords: Advanced practice nurse, Foot care, Older adults, Diabetes mellitus